DOMESTIC TOURISM DEVELOPMENT STRATEGY IN UZBEKISTAN: PROBLEMS, OPPORTUNITIES AND INNOVATIVE SOLUTIONS (Marketing Journal, 2025)
This article examines the theoretical foundations, statistical dynamics, and state policy for the development of domestic tourism in Uzbekistan. It highlights major challenges such as infrastructural deficiencies, low service quality, financial constraints , lack of marketing and information, seasonality, and regional disparities. At the same time, the study outlines key opportunities, including the countryʼs rich cultural and natural heritage, strong governmental support, youth engagement, community -based t ourism initiatives, and international best practices. As innovative solutions, the article proposes digital technologies and platforms, financial incentives, 254 sustainable and “smart” infrastructure, digital marketing strategies, and the development of tourism clusters.
Keywords: domestic tourism; infrastructure; service quality; state policy; innovative solutions; tourism strategy; Uzbekistan